Guidance Note on Letters and Statements Assessing Members' Economic Conditions and Policies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This note provides guidance on the need for, content, review and circulation of assessment letters or statements. Such letters or statements may be prepared for countries with programs supported by the Fund through financial assistance or a policy support instrument, countries receiving Fund emergency assistance, countries with staff-monitored programs (SMPs), or surveillance-only cases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Assessment Letters; Assessment; Letter; Policy; PP